Deciphering Corporate Financial Metamorphosis: A Comprehensive Analysis of Corporate Financial Performances Pre and Post Acquisition - Rafikawaty, Rafikawaty; Hertina, Dede (Devotion : Journal of Research and Community Service, 2024)
This study aims to analyze potential differences in the financial performance of acquiring companies before and after acquisitions, focusing on Liquidity Ratios (Current Ratio and Quick Ratio), Profitability Ratios (Return on Assets Ratio and Net Profit Margin Ratio), Solvency Ratios (Debt to Equity Ratio and Debt to Assets Ratio), Activity Ratio (Total Assets Turnover Ratio and Fixed Assets Turnover Ratio), and Market Ratio (Earning per Share Ratio and Price Earnings Ratio). The research methodology involves a Quantitative Descriptive and Comparative approach, along with an Event Study comparing the financial performance of companies three years before and after the acquisition. Statistical tests, including Sample Paired t-Test and Wilcoxon Signed Rank Test, were conducted using the EViews application on seven acquiring companies listed on the IDX from 2017 to 2023. The findings indicate a significant difference in the company's financial performance before and after the acquisition, specifically in terms of Return on Assets, while the other financial ratios showed no significant differences before and after the acquisition is conducted. The implications of this study are expected to provide in-depth knowledge about the significance of differences in the company's financial performance before and after the acquisition, which will serve as a basis for decision making for investors and public in general.